Pengaruh Profitabilitas, Company Growth, Leverage dan Ukuran Perusahaan Terhadap Penerimaan Opini Audit Going Concern - Amelia Dhea Pramuditha; Ceacili Srimindarti (Universitas Muhammadiyah Metro, 2026)
Investors invest their capital in companies, so they have the responsibility to consider the company's financial statements to obtain information about the company's survival. This test was conducted to analyze how profitability, company growth, leverage and company size affect the going concern audit opinion of manufacturing companies listed on the Indonesia Stock Exchange in 2018-2022. Purposive sampling method was used as a sample collection technique and resulted in a sample of 46 companies. Data sources are obtained from secondary data with a quantitative approach. The analysis used logistic regression with SPSS 20 software. The results show that profitability, company growth and company size do not affect going concern audit opinion. While leverage positively affects going concern audit opinion.